Simulation and Skills Development: Preparing Australian Social Work Education for a Post-COVID Reality. Issue 4 (2nd October 2022) - Jefferies, Gerard; Davis, Cindy; Mason, Jonathan
ABSTRACT: Social work field education is facing unprecedented challenges (e.g., increasing student numbers and limited availability of complex scenario placements due to the COVID pandemic). Students need skills in complex scenarios, but exposure to these situations are limited in available placements. This article explored the literature on using simulation in Australian social work education and addressed the challenges and opportunities surrounding this emerging technology. The results revealed a significant gap in the literature on simulation in social work education, which supports the need for exploring and testing authentic simulation-based learning. Effective methods to assess and support students' practice competencies are critical for ethical and effective pedagogies. IMPLICATIONS Social work students often embark upon placement without an opportunity to develop skills in an authentic scenario, resulting in the potential risk of students being inadequately prepared. The social work profession must prepare for a new COVID reality where face-to-face field practicums with clients may not be possible. Research has shown that social work students are often not provided with the opportunity to engage in complex direct practice situations.